Human chorionic gonadotropin alpha-subunit in rectal carcinoids. Its mode of presence and the change of granule morphology. - Fukayama, M. (1989)
To investigate the nature of endocrine cells immunoreactive for human chorionic gonadotropin alpha-subunit (hCG alpha), rectal carcinoid tumors were studied with immunohistochemistry and immunoelectron microscopy. There were two types of rectal carcinoids: Type A (n = 5) was diffusely argyrophilic and immunoreactive for serotonin with many hCG alpha-positive cells (16.7%-91.1%). Type B (n = 5) was dispersedly argyrophilic and contained, at most, 5% positive cells for pancreatic polypeptide (PP) with hCG alpha cells in 1.4% to 9.7%. By double immunostaining, 55.0% to 89.7% of hCG alpha cells were synchronously immunoreactive for serotonin in Type A and 3.2% to 11.8% of hCG alpha cells showed PP-positivity in Type B. HCG alpha-positive granules had a constant relationship between perimeter (P) and area (A), log10 A approximately D log10 P, in each case (n = 5). The inverse correlation was found between the value of D and the frequency of hCG alpha in the tumor or in the neoplastic cells (P less than 0.05). HCG alpha may represent the quantitative difference of rectal carcinoids and its expression may have some relation with granule morphology in neoplastic endocrine cells of the rectum.